Análise da mortalidade neonatal entre 1998 e 2017 no estado de Minas Gerais: diferenças regionais, distribuição de leitos e aspectos dos serviços de terapia intensiva - Carvalho, Isabella Aline (2020)
Despite the decline in the infant mortality rate observed over the last decade in Brazil and worldwide, the neonatal component of this health indicator remains comparatively high, characterizing a serious Public Health problem in the country and in the state of Minas Gerais (MG). Neonatal deaths, those that occur up to 28 days after birth, are considered preventable and are related to inadequate health policies. The present study aimed to analyze the historical series of neonatal mortality between 1998 and 2017 in MG, as well as to understand aspects related to regionalization and neonatal intensive care assistance in the state and in its health macro-regions. An ecological time series study was carried out using secondary data from IBGE, CNES and SIS (SINASC and SIM), and, subsequently, an individual cross-sectional study with the application of a questionnaire to the intensive care units of MG. In the state, neonatal mortality fell from 14.93 ‰ in 1998 to 8.48 ‰ in 2017 (p <0.01). The mean of this rate was 10.75 ‰ with the weight of the neonatal component being higher than that of the late neonatal component (8.45 ‰ and 2.29 ‰, respectively). Throughout the series of studies, the North Triangle macro-region had the lowest neonatal mortality rates and the Northeast the highest. The Centro macro-region, where the capital Belo Horizonte is located, has the largest number of neonatal ICU beds in the state, which remain concentrated in the largest cities. In 2017, the proportion of “neonatal ICU beds by number of live births” in MG (3.3 ‰) met the recommendations of the Brazilian Ministry of Health (Ordinance GM/MS No. 930, 05/10/2012), but there were still four macro-regions with less than ideal proportions (ie, Northeast, East, West and Center-South). The reduction in neonatal mortality in the state over the studied time series was significant, which may be related to the increase in the number of neonatal ICU beds over the years. Aspects related to differences between the components of neonatal mortality (early and late deaths), as well as the importance of factors such as bed distribution, quality of neonatal intensive care units, including characteristics of the service and multidisciplinary team, in the different macro-regions of the state were also discussed.